Natural products possessing protein tyrosine phosphatase 1B (PTP1B) inhibitory activity found in the last decades - Jiang Cheng-shi; Liang Lin-fu; Guo Yue-wei (Acta Pharmacologica Sinica, 2016)
This article provides an overview of approximately 300 secondary metabolites with inhibitory activity against protein tyrosine phosphatase 1B (PTP1B), which were isolated from various natural sources or derived from synthetic process in the last decades. The structure-activity relationship and the selectivity of some compounds against other protein phosphatases were also discussed. Potential pharmaceutical applications of several PTP1B inhibitors were presented.